Alkaline cations directing the transformation of FAU zeolites into five different framework types - Van Tendeloo, Leen; Gobechiya, Elena; Breynaert, Eric; Martens, Johan A; Kirschhock, Christine E A (Chemical communications (Cambridge, England), 2013)
Exposure of faujasite zeolites to different alkali hydroxide solutions readily yields zeolites with ABW, CHA, MER and ANA topologies. In NaOH faujasite persisted. Aside from new opportunities for zeolite synthesis, this reveals that a suitable aluminosilicate connectivity in the source material significantly facilitates zeolite crystallization.